113 ANABOLIC AND ANDROGENIC ACTIVITY OF "DESIGNER STEROID", TETRAHYDROGESTRINONE. (1st January 2005) - Jasuja, R.; Catlin, D. H.; Herbst, K. L.; Chang, Y. C.; Miller, A.; Starcevic, B.; Artaza, J.; Singh, R.; Datta, G.; Sarkissian, A.; Bhasin, S.
Abstract : Since the discovery of THG in 2003, numerous elite athletes have tested positive for its abuse. However, in the absence of documented evidence of its anabolic and androgenic activity in vivo, legal counsels of athletes have challenged the validity of the regulatory ban. In order to determine whether THG is an androgen, we utilized in vitro model of stem cell commitment and differentiation and a castrated rat model to characterize the androgenic activity of THG. In Vitro: Fluorescence polarization assays were utilized to measure relative binding affinity of THG for androgen receptor (AR). Kd's for THG and DHT were found to be 8.8±1.4 and 9.9±1.2 nM respectively. C3H10T1/2 mesenchymal pluripotent cells were treated with THG (0-30 nM) or DHT, (0-30 nM) for 0-14 days, and differentiation was evaluated by quantitating protein, and immunocytochemical staining for early (MyoD) and late (MHC-II) myogenic markers. Similar to DHT, THG induced nuclear translocation of AR and upregulated AR levels. Treatment with graded concentrations of THG or DHT significantly increased the number of MHC+ myotubes. Western blot analysis confirmed that THG dose-dependently increased MyoD and MHC protein expression compared with control. In Vivo: Sprague Dawley male rats were divided into following groups. Dose 1: 375μg/kg and Dose2: 750μg/kg body weight (Table ) Castrate and Sham groups received oil injections. Castration significantly reduced fat free mass (FFM) and levator ani weights and THG administration restored the muscle loss. The androgenic effects of THG on prostate and seminal vesicles; also prevented castration induced attrition. Conclusion: THG binds AR, activates AR-mediated signaling, promotes myogenesis in mesenchymal pluripotent cells in vitro and has anabolic activity in the castrated rat model. Thus, THG is a bone fide androgen.